IDENTIFICATION OF GH|ALUI AND GHR|ALUI GENES POLYMORPHISMS IN INDONESIAN BUFFALO - Andreas, E.; Sumantri, C.; Nuraini, H.; Farajallah, A.; Anggraeni, A. (Diponegoro University, 2010)
Growth hormone (GH) is an anabolic hormone which sintesized and secreted by somatrotop cell inpituitary anterior lobe. GH exert its effect on growth and metabolism by interacting with a specificreceptor on the surface of the target cells. Growth hormone receptor (GHR) has been suggested ascandidate gene for traits related to meat production in Bovidae. The objectives of this study were toidentify polymorphism of GH and GHR genes in buffalo. The 452 DNA samples buffalo were collectedfrom five populations in Indonesia (Siborong-Borong-Medan (65), Lebak-Banten (29), Pandeglang-Banten (180), Semarang-Central Java, and Mataram-West Nusa Tenggara (103)). A gene fragment of theGH|AluI gene at 432 bp located on exon 3 and GHR|AluI gene at 298 bp on exon 10 were successfullyamplified by using the techniques of a PCR (polymerase chain reaction) and genotyped by PCR-RFLP(restriction fragment length polymorphism) then -SSCP (single strand conformation polymorphism). Theresults showed no polymorphisms were detected in these genes. All buffaloes tested had LL genotype forlocus GH|AluI and AA genotype for locus GHR|AluI.